The Influence of Emotional Quotient Level on Employee Performance in the Technical Implementation Unit of Education and Sports Training for Students and Students of Bogor District - Septiawati, Shella; Lutfiani, Maulita (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to investigate the level of emotional quotient (EQ) and its impact on the performance of employees in the Student Sports Education and Training Technical Implementation Unit for Students and Students of Bogor District. The research method employed surveys and data analysis using SPSS. The results indicate that EQ significantly influences the performance of employees in the unit, accounting for 63.8%, while other factors contribute to the remainder. Further analysis using SPSS reveals that emotional intelligence factors, such as emotional stability, emotional strength, and emotional satisfaction, have significant values ​​confirming their impact on performance. These findings provide valuable insights for human resource management in understanding the importance of EQ in enhancing the productivity and quality of employee performance within the organizational environment.